2021
DOI: 10.3390/s21113631
|View full text |Cite
|
Sign up to set email alerts
|

UWB Radio-Based Motion Detection System for Assisted Living

Abstract: Because of the ageing population, the demand for assisted living solutions that can help prolonging independent living of elderly at their homes with reduced interaction with caregivers is rapidly increasing. One of the most important indicators of the users’ well-being is their motion and mobility inside their homes, used either on its own or as contextual information for other more complex activities such as cooking, housekeeping or maintaining personal hygiene. In monitoring users’ mobility, radio frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Taking into account the time of the measurement and the final number of stored CIRs, it was found that the real time difference between the data records in the computer memory was about 124 ms. This value is close to the value of the impulse response saving period of 133 ms, which was used in [37].…”
Section: Measurement Scenariossupporting
confidence: 62%
“…Taking into account the time of the measurement and the final number of stored CIRs, it was found that the real time difference between the data records in the computer memory was about 124 ms. This value is close to the value of the impulse response saving period of 133 ms, which was used in [37].…”
Section: Measurement Scenariossupporting
confidence: 62%
“…15.4; among other topics, it is looking into sensing (radar) applications of HRP, such as presence detection. The presence detection has been previously implemented [5] by using DW1000 [6], an IEEE 802.15.4-2015 HRP [1] compliant device, that does SHR-based CIR estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults’ daily routines and movement patterns are important in healthcare applications, since they may help identify changes in habits, odd actions, or a worsening state of health. Such information must be shared with caretakers, physicians, or other members of the user’s social network [ 2 ]. The architecture of the proposed AAL technology over the IoMT framework is presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%